The Utility of Transcranial Stimulated Motor-Evoked Potential Alerts in Cervical Spine Surgery Varies Based on Preoperative Motor Status. Issue 23 (1st December 2022) - Funaba, Masahiro; Kanchiku, Tsukasa; Kobayashi, Kazuyoshi; Yoshida, Go; Machino, Masaaki; Yamada, Kei; Shigematsu, Hideki; Tadokoro, Nobuaki; Ushirozako, Hiroki; Takahashi, Masahito; Yamamoto, Naoya; Morito, Shinji; et al.
Abstract : Study Design: A prospective multicenter observational study. Objective: The aim was to investigate the validity of transcranial motor-evoked potentials (Tc-MEP) in cervical spine surgery and identify factors associated with positive predictive value when Tc-MEP alerts are occurred. Summary of Background Data: The sensitivity and specificity of Tc-MEP for detecting motor paralysis are high; however, false-positives sometimes occur. Materials and Methods: The authors examined Tc-MEP in 2476 cases of cervical spine surgeries and compared patient backgrounds, type of spinal disorders, preoperative motor status, surgical factors, and the types of Tc-MEP alerts. Tc-MEP alerts were defined as an amplitude reduction of more than 70% from the control waveform. Tc-MEP results were classified into two groups: false-positive and true-positive, and items that showed significant differences were extracted by univariate analysis and detected by multivariate analysis. Results: Overall sensitivity was 66% (segmental paralysis: 33% and lower limb paralysis: 95.8%) and specificity was 91.5%. Tc-MEP outcomes were 33 true-positives and 233 false-positives. Positive predictive value of general spine surgery was significantly higher in cases with a severe motor status than in a nonsevere motor status (19.5% vs . 6.7%, P =0.02), but not different in high-risk spine surgery (20.8% vs . 19.4%). However, rescue rates did not significantly differ regardless of motor status (48% vs . 50%). In a multivariate logistic analysis, a preoperative severe motor status [ P =0.041, odds ratio (OR): 2.46, 95% confidence interval (95% CI): 1.03–5.86] and Tc-MEP alerts during intradural tumor resection ( P <0.001, OR: 7.44, 95% CI: 2.64–20.96) associated with true-positives, while Tc-MEP alerts that could not be identified with surgical maneuvers ( P =0.011, OR: 0.23, 95% CI: 0.073–0.71) were associated with false-positives. Conclusion: The utility of Tc-MEP in patients with a preoperative severe motor status was enhanced, even in those without high-risk spine surgery. Regardless of the motor status, appropriate interventions following Tc-MEP alerts may prevent postoperative paralysis.